Evaluation of effect of low-level laser therapy on alleviation of pain in patients with implant-supported mandibular overdenture: A pilot study - Raveena Makker; Rajeev Srivastava; Sourabh Khandelwal; Prashanthi Reddy (The Journal of Indian Prosthodontic Society)
Aim: Rehabilitation of edentulous jaws with implant-supported overdenture has achieved a comprehensive acclamation across the globe due to compromised retention and stability in conventional complete dentures. In dentistry, low-level laser therapy (LLLT) has become a viable treatment option for lowering inflammation, easing pain, and speeding up wound healing. This study aimed to evaluate the effect of LLLT on alleviation of pain in patients with two implant-supported mandibular overdentures. Study Setting and Design: This study was carried out in the Department of Prosthodontics at Index Institute of Dental Sciences, Indore, Madhya Pradesh. Completely edentulous patients willing for implant-supported mandibular overdenture and who gave consent, were enrolled. Materials and Methods: A total of ten implants were placed in five patients with completely edentulous mandibular arch willing for implant-supported mandibular overdenture. Individuals from the outpatient division of Department of Prosthodontics, Crown & Bridge, Index Institute of Dental Sciences, Indore were chosen as patients. Bilateral implants were inserted into the mandible at locations B and D. On the experimental side, low-level laser therapy (wavelength 810 nm) was administered immediately following implant insertion and on the third day. Over the course of 72 hours, pain after surgery was assessed using visual analogue scale (VAS) values, beginning at baseline. Statistical Analysis Used: The Mann-Whitney U test was used for statistical analysis of the intergroup pain alleviation scores. Results: The results showed that on intergroup comparison, the experimental side exhibited significantly reduced VAS pain scores relative to the control side (P<0.05). Conclusion: LLLT can be used as a promising adjuvant therapy to lower the degree and duration of pain after undergoing dental implant surgery.